Parental concerns towards children and adolescents with epilepsy in Sri Lanka—Qualitative study. (January 2016) - Murugupillai, Roshini; Wanigasinghe, Jithangi; Muniyandi, Ravi; Arambepola, Carukshi
Graphical abstract: Highlights: Major parental concerns were safety, education, employment & marriage prospect. Unpredictability of seizures, stigma & unawareness influence parental concerns. Epileptic children are denied of certain food due to false beliefs. Abstract: Purpose: Social, cultural, psychological and many other factors significantly impact the lives of epileptic children and their families. Parental concerns towards their children are less known in south Asian children with epilepsy. We aimed to identify the parental concerns regarding their children and adolescents with epilepsy in Sri Lanka. Methods: We carried out qualitative study in 3 districts of Sri Lanka, comprising 16 in-depth interviews with parents of children and adolescents with epilepsy and 3 focus group discussions with primary caregivers of epileptic children and key informants (schoolteachers, public health staffs). Content analysis of the interview data was performed. Results: Parental concerns were spread among seven themes that emerged from the content analysis. These concerns were about the child's functioning in areas such as physical, behavioural, psychological and social, education, concerns related to anti-epileptic therapy and epilepsy as a disease. Parents were more concerned about their child's safety, educational achievements and future prospects in terms of employment and marriage. Unpredictability of seizures, fear of stigma and unawareness of epilepsy were the main reasons voiced by the parents for having such concerns. Increased concern and perception of vulnerability was seen among parents whose children had epilepsy and co-morbid illness. Conclusions: Parental concerns towards their children and adolescents show a multidimensional construct. Unpredictability of seizures, fear of stigma and unawareness of epilepsy were identified as key influential factors in moulding the parental concerns.